KONSEP PENYATUAN MANUSIA DENGAN KRISTUS MENURUT HILARION ALFEYEV: CINTA MANUSIA KEPADA ALLAH MENGHASILKAN PENGILAHIAN - Halawa, Ririn Valentina (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Salvation is a gift that comes from the redemption of Jesus Christ. However, mankind does many things against the will of God. For humans, salvation is determined by good deeds. However, Hilarion Alfeyev in the book Othodox Christianity says that salvation is a gift free from sin. The purpose of this article is to contribute to the human need to respond not only by doing good, but also by believing, repenting from bad actions to good actions. In making the article using the literature method. Where the author uses books, journal articles as references to solve the problems in the article discussed. The results of this study are about salvation according to Hilarion Alfeyev, namely, salvation is theosis, theosis occurs thanks to human love for God and the goal of man after salvation is to be one with Christ. As a result of the salvation response, humans will experience glorification.